The Influence Of Infrastructure, Human Resources, Work Environment, Motivation, Standard Operating Procedures, And Work Discipline On The Work Effectiveness Of Class Iib Correctional Institution Employees - Titi Hasanah; Herliansyah Herliansyah; Markus Markus (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to identify and analyze the influence of infrastructure, human resources, work environment, motivation, standard operating procedures, and work discipline both individually and collectively on the work effectiveness of employees at the Class IIB Muara Enim Correctional Institution. The research applies a quantitative approach by distributing questionnaires to respondents as the primary data collection method. Data quality was examined through validity, reliability, and normality tests, while the analysis was conducted using both descriptive and inferential statistics, including multiple regression analysis, partial (t-test), simultaneous (F-test), and the coefficient of determination (R²). The findings indicate that each independent variable namely infrastructure, human resources, work environment, motivation, standard operating procedures, and work discipline has a positive and significant influence on employee work effectiveness. Furthermore, when tested simultaneously, these variables collectively demonstrate a strong and significant impact on the overall work effectiveness of employees at the Class IIB Muara Enim Correctional Institution.